Utilizing E-teaching Activities to Enhance English Majors' Speaking Skills in Pandemic Era - Lisa Rakhmanina; Melati Melati (English Education Study Program Faculty of Teacher Training and Education, 2022)
In the framework of the COVID-19 pandemic, all universities in the province of Bengkulu have paid special attention to the implementation of E-teaching activities. The purpose of this study is to assess the importance of E-activities on the speaking skills of second-year English majors at three private universities in Bengkulu. A survey was done on a group of 15 teachers and 100 students in terms of determining the facts. The findings suggested that the school's information technology infrastructure met the requirements for online education. Most teachers have mastered E-teaching equipment, particularly supporting software, and have adapted their teaching approaches to the online teaching model in order to polarize learners' learning activities. In addition, the majority of students actively participate in the learning process through E-teaching, activities, and answering questions presented by teachers. However, some teachers are still conscious of carrying out this responsibility and drafting courses. This study provides feasible and appropriate strategies to enhance E-teaching at private universities in Bengkulu.